Suppression of cross-band scattering in interleaved dual-band cellular base-station antenna arrays - Sun, Hai-Han (2021)
In this article, novel techniques to suppress cross-band scattering in interleaved dual-band base station antenna arrays are presented. Firstly, the detrimental effect of high-band (HB) elements on low-band (LB) radiation performance is theoretically analyzed. With a thorough analysis, a capacitance-loaded HB element is innovated to solve the issue and restore the LB patterns. Secondly, to eliminate the reverse HB scattering caused by the LB element while enhancing the bandwidth of the LB element, a novel double-arm choked cross-dipole configuration is proposed. A compact array section is built with these innovated elements. The experimental results of the array show a largely suppressed cross-band scattering with stable radiation performance across the well-matched bands, demonstrating the effectiveness of the presented techniques.